[6+3] cycloaddition of fulvenes with 3-oxidopyrylium betaine: a novel methodology for the synthesis of fused cyclooctanoid natural products - Radhakrishnan, K. V.; Krishnan, K. Syam; Bhadbhade, Mohan M.; Bhosekar, Gaurav V. (Tetrahedron Letters, 2005)
Fulvenes undergo an easy [6+3] cycloaddition with 3-oxidopyrylium betaines leading to 5-8 fused oxabridged cyclooetanoids. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: cyclooctanoids; fulvenes; oxidopyrylium betaines; [6+3] cycloaddition

[6+3] cycloaddition of pentafulvenes with 3-oxidopyrylium betaine: a novel methodology toward the synthesis of 5-8 fused oxabridged cyclooctanoids - Krishnan, K. Syam; Sajisha, V. S.; Anas, S.; Suresh, C. H.; Bhadbhade, Mohan M.; Bhosekar, Gaurav V.; Radhakrishnan, K. V. (Tetrahedron, 2006)
Pentafulvenes undergo a facile [6+3] cycloaddition with 3-oxidopyrylium betaine, generated from the corresponding pyranulose acetate, leading to the formation of 5-8 fused oxabridged cyclooctanoids. The product is formed by a [6+3] cycloaddition, followed by a 1,5-hydrogen shift of the initially formed [6+3] adduct. The reaction was found to be general and a number of fulvenes with a wide range of substituents at the exocyclic double bond, that is, at the C6 position followed a similar reactivity pattern. The [6+3] adduct, a 5-8 fused oxabridged cyclooctanoid, is potentially amenable to a number of synthetic transformations due to the presence of an alpha, beta-unsaturated ketone and cyclopentadiene part. By selecting appropriately substituted fulvene and pyranulose acetates, it is possible to use this methodology for the synthesis of a wide range of 5-8 fused cyclooctanoids. The experimental results have been rationalized on the basis of theoretical calculations. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: fulvenes; oxabridged cyclooctanoids; oxidopyrylium betaine; [6+3] cycloaddition